USLUB AL AMR DALAM SURAT YASIN - Daulay, Irmasani; Linur, Rahmat (AL MA'ANY, 2023)
The Al-Qur'an employs language in a remarkably eloquent manner, carefully selecting appropriate words where each holds its own significance. Some scholars argue that the Qur'an possesses a profound balaghah value that is unparalleled. Thus, the purpose of this paper is to examine this linguistic style, particularly the language style of Amr, which encompasses both its essential (original) meaning and its figurative (majazi) meaning. Surah Yasin is classified as a Makkiyah Surah because it was revealed in the city of Mecca. This Surah encompasses admonitions from Allah SWT and His Messenger, instructions for worshipping Allah SWT, retribution for believers and disbelievers, manifestations of Allah SWT's power, and warnings from the Prophet about Hell. It is named Yasin due to its opening with the letters Yaasiin. According to the interpretation provided by the Ministry of Religion, just as the meanings of the alphabet letters are present at the beginning of several Surahs in the Qur'an, so too does Yaasiin hold significance within the verses at the start of this Surah, indicating that significant matters will be discussed subsequently. Allah solemnly swears by the Qur'an that Muhammad SAW is truly His messenger sent to a people who had not previously received any messengers. Within this Surah, the author identifies approximately 11 instances of al-Amr forms, each with its intrinsic or figurative meaning. Consequently, the author is intrigued to conduct a deeper study, analyze, and map the occurrences of al-Amr in Yasin based on their respective parts and meanings. This written work adopts an analytical descriptive approach. Materials and research sources obtained through library research will be detailed, described, and analyzed, after which the findings will be presented in written form to provide a comprehensive depiction of the uslub al-Amr form in Surah Yasin. Keywords: Style, al-amr, yasin.